Prophecy - Oh, Ellen (The dragon king chronicles, 2013)
"A demon slayer, the only female warrior in the King's army, must battle demon soldiers, an evil shaman, and the Demon Lord to find the lost ruby of the Dragon King's prophecy and save her kingdom"--